Oceanographic data of Time Series Station Spiekeroog for 2012 - Thomas Henry Badewien; Axel Braun; Andrea Lübben; Oliver Zielinski (PANGAEA, 2025)
The Time Series Station Spiekeroog (TSS) was setup in 2002, in the tidal inlet between the East Frisian Islands of Langeoog and Spiekeroog in the Southern German Bight, at position 53°45'01.0'' N, 007°40'16.3'' E. The aim was to ensure the continuous measurement of physical, biological, chemical and meteorological parameters, even under extreme weather conditions such as storms, ice, and storm surges. The TSS was financed as part of the Deutsche Forschungsgemeinschaft (DFG) research unit BioGeoChemistry of Tidal Flats and the Ministry for Science and Culture of the Land of Lower Saxony (MWK). Here, sea level, water temperature and conductivity were measured in the year 2012. All raw data were revised and corrected for steps as range, outliers and stationarity checks. Water temperature and conductivity were measured in five different depths (4 m, 5.5 m, 7.5 m, 9.5 m, 11.5 m below MSL). Due to marine biofouling at the sensors and accompanying drift of instruments, the measured water temperature and conductivity data were corrected via linear regression by using reference data. As the water column in this region is well mixed and the water depth of the measurements varies with the tide, data from all five depths were averaged and referenced to a water depth of 4 m. Absolute salinity was derived from conductivity, temperature and pressure data according to TEOS 10. Data were smoothed and a quality flag was assigned for water temperature and salinity. The quality flags refer to the standard for data quality control of SeaDataNet https://www.seadatanet.org/ (0 = raw data, 1 = good data, 2 = probably good data, 3 = questionable data).. A detailed description of the Time Series Station Spiekeroog, its structure and instrumentation can be found in Zielinski et al. (2022) and in Reuter et al. (2009).